PENGARUH IKLAN RADIO DAN PERILAKU PENDENGAR STUDI PADA IKLAN RADIO DAN PERILAKU PENDENGAR DALAM ACARA DAKWAH ISLAM DI RADIO RASETA FM MALANG - Fauzi, Ahmad (INTAJ, 2018)
In the field of marketing, it is in need of adequate media to convey its business promotional messages. The atmosphere of competition makes various promotional patterns to attract consumers as much as possible. Advertising, for example, this one has the characteristics and need a delicate consideration for the selection of suitable media. Advertising media that is common instead of television and print is radio. Radio ads have their own characteristics compared to other media. The companys effort to create satisfaction can be done through the quality of service provided. The maximum quality of service directly can give the maximum consumers expectation. By having good service quality then they can fulfil all forms of demand for products or services offered to consumers. Quality of service in accordance with the expectations of consumers by itself will support the companys efforts in order to achieve the goals set by the company both short and long-term, including in the business of radio broadcasting. In the end, it can influence the listener behaviour. Dawah is the way to invite, call and influence people to always adhere to the teachings of Allah SWT in order to obtain the happiness of life in the world and hereafter. Inviting to the way of Allah SWT is our obligation. The success of his invitation reflects the prospect and preservation of future Islamic developments, for the advancement and retreat of religion rests with the adherents of His followers. Keywords: radio advertising, listener behavior, dawah